2009
DOI: 10.1104/pp.109.138164
|View full text |Cite
|
Sign up to set email alerts
|

Strain Mechanosensing Quantitatively Controls Diameter Growth and PtaZFP2 Gene Expression in Poplar

Abstract: Mechanical signals are important factors that control plant growth and development. External mechanical loadings lead to a decrease in elongation and a stimulation of diameter growth, a syndrome known as thigmomorphogenesis. A previous study has demonstrated that plants perceive the strains they are subjected to and not forces or stresses. On this basis, an integrative biomechanical model of mechanosensing was established ("sum-of-strains model") and tested on tomato (Solanum lycopersicum) elongation but not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 36 publications
2
72
1
Order By: Relevance
“…Poplar stem bending caused a complete cessation of cambial growth during the first hours [4]. The coincidence of early growth cessation in bent poplar and transitory overexpression of genes related to plant defence is consistent with the reported antagonism between plant immunity and growth [41].…”
Section: Discussionsupporting
confidence: 65%
“…Poplar stem bending caused a complete cessation of cambial growth during the first hours [4]. The coincidence of early growth cessation in bent poplar and transitory overexpression of genes related to plant defence is consistent with the reported antagonism between plant immunity and growth [41].…”
Section: Discussionsupporting
confidence: 65%
“…Although it is difficult to disentangle mechanical effects from other environmental stimuli, such a response might involve as much as 2.5% of the Arabidopsis genome [37] and in particular Ca 2+ -dependent proteins, like TOUCH3 (TCH3). In poplar, the expression of the ZFP2 transcription factor occurs in a few minutes following mechanical stimulation, the level of the protein being quantitatively related to the amount of stem bending [38]. Many mechanosensitive ion channels have been identified [39,40], as well as a plasma membrane protein (MCA1) correlating Ca 2+ influx with mechanostimulation [41], which supports the belief that calcium is central to mechanosensing [40].…”
Section: Providing Positional Information Through Mechanical Forcesmentioning
confidence: 83%
“…Though, the stem elongation zone is far away from the bending site, indicating that the response zone can be at a long distance from the perception zone of the mechanical stimuli [163]. Based on controlled bending experiments, Coutand et al [165] showed that the mechanosensing and responses depend on the load, the mechanical structure of the organ and the mechanosensitive structure, that is the location and amount of mechanosensitive tissues involved in the response. They demonstrated that the variable which is perceived is the strain and that the duration of the plant response is correlated to the spatial sum of longitudinal strains in the bent part.…”
Section: D) Mechanoperception and Signalling Pathwaysmentioning
confidence: 99%